Case Study : Job Selection and Career planning: Unwinding the dilemma - Padaguri, Vijay G (Journal of Contemporary Research in Management (JCRM), 2013)
Most of the people face career related dilemmas in the contemporary corporate scenario. This is due several factors like the wider range of choices available to them, internally in terms of different verticals and externally in terms of the plethora of companies, both established and start-ups who are on a constant look-out for talent acquisition. The dilemma is more intense and confusing for the B-School students. Making career decisions can be like a walk on the tight-rope due to lack ofÂ experience and multiple, conflicting sources of information. They need to understand the factors that need to be taken into consideration while selecting their first job, prioritization of the job related factors and theÂ decision making process. Proper career planning isnâ€™t easy and involves a lot of thought and right execution of ideas and decisions.Even afterÂ getting the first job, people may want to change. The job may not meetÂ their expectations or they may not meet the expectations of the job or the company. One of the typical examples is a sales job. But they need to make the changes necessary and carry on. This case is a hypotheticalÂ case that tries to explore the career confusions and ways to deal with the career confusions. It also throws some light on mid-career changes and adapting to new environments and new responsibilities. The case is written in a dialogue format between the three characters of the case, Vinay,Â Mukul and Vamsh. The case transcends across areas of recruitment andÂ selection, individual and organization behavior and personal growth andÂ inert-personal effectiveness. The prime motive is to bring out careerÂ confusion scenarios and also solutions. Note:This case was awarded the First Prize in â€œBench Mark-2011â€ a National Level Case Writing Competition, conducted on 25th February 2011 at PSG Institute of Management.